Good Governance for Sustainable Development: Municipal Waste Management - Demeiati Nur Kusumaningrum; Peggy Puspa Haffsari (Universitas Bosowa, 2017)
This paper explores the management of waste and strategies in dealing with environmental problems. The increasing tourism activities and the weakness of garbage management in traditional markets are the challenges of waste management in Batu City. While, the industrial waste of Malang Regency generates social protest and bring the disadvantages on the quality of water of Brantas River. The practice on sustainable development model required the roles of state to achieve society welfare by considering economic, social, and ecological dimensions. This study examine the policy making and institutional coordination as the efforts to perform good governance principles. The government of Batu City invest on sewage treatment plant in Tlekung dump landfill (Tempat Penampungan Akhir-TPA) to produce liquid fertilizer and methane gas as the end of its process. Monitoring and evaluation on industrial waste management system (IPAL) becomes the policy of Malang Regency to preserve the quality of water. The parliament members gain the manufacture industry owner’s attention on waste responsibility through visiting and socialization programs.